2017
DOI: 10.1016/s0140-6736(16)30958-8
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer: current therapies and new targeted treatments

Abstract: Lung cancer is the most frequent cause of cancer-related deaths worldwide. Every year, 1·8 million people are diagnosed with lung cancer, and 1·6 million people die as a result of the disease. 5-year survival rates vary from 4-17% depending on stage and regional differences. In this Seminar, we discuss existing treatment for patients with lung cancer and the promise of precision medicine, with special emphasis on new targeted therapies. Some subgroups, eg-patients with poor performance status and elderly patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
2,030
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,584 publications
(2,053 citation statements)
references
References 147 publications
4
2,030
0
19
Order By: Relevance
“…The main classification of lung cancer includes small cell lung carcinoma (SCLC) and non-small cell lung cancer (NSCLC) (2). NSCLC, which accounts for 85% of all lung cancers, primarily comprises adenocarcinoma, squamous cell carcinoma, large cell carcinoma, sarcomatoid carcinoma, and adenosquamous cell carcinoma, among which lung adenocarcinoma is one of the most aggressive histological types in lung cancer and is the main subtype of NSCLC (3).…”
Section: Introductionmentioning
confidence: 99%
“…The main classification of lung cancer includes small cell lung carcinoma (SCLC) and non-small cell lung cancer (NSCLC) (2). NSCLC, which accounts for 85% of all lung cancers, primarily comprises adenocarcinoma, squamous cell carcinoma, large cell carcinoma, sarcomatoid carcinoma, and adenosquamous cell carcinoma, among which lung adenocarcinoma is one of the most aggressive histological types in lung cancer and is the main subtype of NSCLC (3).…”
Section: Introductionmentioning
confidence: 99%
“…ALK inhibitors (alectinib, ceritinib, and crizotinib) and EGFR inhibitors (afatinib, erlotinib, gefitinib, and osimertinib) are approved for the treatment of lung cancer patients with ALK fusions and EGFR mutations, respectively [16,17]. In contrast, FGFR inhibitors, such as AZD4547 [18], derazantinib (ARQ 087) [19], erdafitinib (JNJ-42756493) [20], infigratinib (BGJ398) [21], and LY2874455 [22], are in clinical trials for the treatment of cancer patients with alterations in FGFR family genes [23].…”
Section: Genomic Tests For Personalized Medicinementioning
confidence: 99%
“…By activating the immune system to recognize and eliminate cancer, immune checkpoint blockade has the potential to elicit durable responses and augment survival outcomes for a subset of patients [1,2]. In addition, the ability of radiotherapy to induce an immunogenic response and neutralize the immune-suppressive effects of the tumor microenvironment, uniquely positions it as a synergistic tool at the center of emerging multimodal therapies utilizing immune checkpoint blockade [3][4][5][6][7].Immune checkpoint inhibitors of the PD-1/PD-L1 pathway have emerged as a promising new therapeutic strategy [8][9][10][11]. These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16].…”
mentioning
confidence: 99%
“…Immune checkpoint inhibitors of the PD-1/PD-L1 pathway have emerged as a promising new therapeutic strategy [8][9][10][11]. These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16].…”
mentioning
confidence: 99%